Neuromuscular electrical stimulation is feasible in patients with acute heart failure. (28th August 2019) - Kondo, Toru; Yamada, Sumio; Tanimura, Daisuke; Kazama, Shingo; Ishihara, Toshikazu; Shimojo, Masafumi; Iwata, Etsuo; Kondo, Sayano; Hiraiwa, Hiroaki; Kato, Toshiaki; Sano, Hiroaki; Awaji, Yoshifumi; et al.
Abstract: Aims: In acute heart failure (AHF), immobilization is caused because of unstable haemodynamics and dyspnoea, leading to protein wasting. Neuromuscular electrical stimulation (NMES) has been reported to preserve muscle mass and improve functional outcomes in chronic disease. NMES may be effective against protein wasting frequently manifested in patients with AHF; however, whether NMES can be implemented safely without any adverse effect on haemodynamics has remained unknown. This study aimed to examine the feasibility of NMES in patients with AHF. Methods and results: Patients with AHF were randomly assigned to the NMES or control group. The intensity of the NMES group was set at 10–20% maximal voluntary contraction level, whereas the control group was limited at a visible or palpable level of muscle contraction. The sessions were performed 5 days per week since the day after admission. Before the study implementation, we set the feasibility criteria with following items: (i) change in systolic blood pressure (BP) > ±20 mmHg during the first session; (ii) increase in heart rate (HR) > +20 b.p.m. during the first session; (iii) development of sustained ventricular arrhythmia, atrial fibrillation (AF), and paroxysmal supraventricular tachycardia during all sessions; (iv) incidence of new‐onset AF during the hospitalization period < 40%; and (v) completion of the planned sessions by >70% of patients. The criteria of feasibility were set as follows; the percentage to fill one of (i)–(iii) was <20% of the total subjects, and both (iv) and (v) were satisfied. A total of 73 patients (median age 72 years, 51 men) who completed the first session were analysed (NMES group, n = 34; control group, n = 39). Systolic BP and HR variations were not significantly different between two groups (systolic BP, P = 0.958; HR, P = 0.665). Changes in BP > ±20 mmHg or HR > +20 b.p.m. were observed in three cases in the NMES group (8.8%) and five in the control group (12.8%). New‐onset arrhythmia was not observed during all sessions in both groups. During hospitalization, one patient newly developed AF in the NMES group (2.9%), and one developed AF (2.6%) and two lethal ventricular arrhythmia in the control group. Thirty‐one patients in the NMES group (91%) and 33 patients in the control group (84%) completed the planned sessions during hospitalization. This study fulfilled the preset feasibility criteria. Conclusions: NMES is feasible in patients with AHF from immediately after admission.